2011
DOI: 10.1002/esp.2144
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of doline geometry using geophysics on the Quercy plateau karst (South France)

Abstract: In the protection of karstic aquifers, the role played by dolines is of interest as these shallow structures can be preferential infiltration pathways for groundwater recharge. In this study, three depressions in South France (Orniac, Lot) were identified and characterized using combined geophysical methods. Apparent conductivity mapping allows precise definition of dolines corresponding to topographic depressions. It also reveals other dolines that are hidden by soil cover. Electrical resistivity and seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 25 publications
0
28
0
1
Order By: Relevance
“…Gutiérrez et al, 2014). Most investigations dealing with sinkhole characterization using subsurface methods have focussed on collapse sinkholes underlain by cavernous carbonate bedrock, and utilize near-surface geophysical methods in combination with geotechnical boreholes (van Schoor, 2002;Zhou et al, 2002;Kruse et al, 2006;Valois et al, 2011;Festa et al, 2012;Nouioua et al, 2013;Youssef et al, 2013). Most investigations dealing with sinkhole characterization using subsurface methods have focussed on collapse sinkholes underlain by cavernous carbonate bedrock, and utilize near-surface geophysical methods in combination with geotechnical boreholes (van Schoor, 2002;Zhou et al, 2002;Kruse et al, 2006;Valois et al, 2011;Festa et al, 2012;Nouioua et al, 2013;Youssef et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gutiérrez et al, 2014). Most investigations dealing with sinkhole characterization using subsurface methods have focussed on collapse sinkholes underlain by cavernous carbonate bedrock, and utilize near-surface geophysical methods in combination with geotechnical boreholes (van Schoor, 2002;Zhou et al, 2002;Kruse et al, 2006;Valois et al, 2011;Festa et al, 2012;Nouioua et al, 2013;Youssef et al, 2013). Most investigations dealing with sinkhole characterization using subsurface methods have focussed on collapse sinkholes underlain by cavernous carbonate bedrock, and utilize near-surface geophysical methods in combination with geotechnical boreholes (van Schoor, 2002;Zhou et al, 2002;Kruse et al, 2006;Valois et al, 2011;Festa et al, 2012;Nouioua et al, 2013;Youssef et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nyquist et al (2007) indicated that a soil-bedrock interface provides resistivity of 1000 Ω•m on a karst terrain in eastern Pennsylvania. Valois et al (2011) also interpreted a layer with 1000 Ω•m resistivity as clayey sediment that filled a bedrock depression in a karst region in SW France.…”
Section: Electrical Resistivity Tomographymentioning
confidence: 99%
“…Dolines play an important role in karst hydrogeology as they are often preferential infiltration pathways for groundwater recharge (Valois et al . ). Furthermore, the spatial distribution of dolines can provide very valuable information on neotectonics when appropriate methods of analysis are employed (Faivre and Reiffsteck ).…”
Section: Introductionmentioning
confidence: 97%
“…Although the structure of doline filling can be investigated by geophysical methods (Valois et al . ), the usual morphometric analysis only involves the depressions themselves (number, spatial location and pattern, orientation, depth, size, shape and altitude above sea level) and this information can be easily obtained from a number of different sources (Wu et al . ).…”
Section: Introductionmentioning
confidence: 99%